First record of species of Cerambycidae (Coleoptera) in cardeiro (Scleronema micranthum) (Bombacaceae) in the Central Amazon - Abreu, Raimunda L.S.; Ronchi-Teles, Beatriz; Monné, Miguel Angel; Vianez, Basílio Frasco (Neotropical Entomology, 2009)
The occurrence of Cerambycidae (Lamiinae) was evaluated in trunk and branch samples of cardeiro (Scleronema micranthum), a forest species from the Central Amazon. Samples were exposed to biodegradation for 24 months on the forest soil, during which adults and larvae were collected and their attack was evaluated. From a total of 643 cerambycids collected, 606 were immatures and 37 were adults. Two species of Acanthoderini, Psapharochrus longispinis (Bates) (17 specimens) and Steirastoma melanogenys White (17 specimens) were collected, as well as one species of Onciderini, Jamesia globifera (Fabricius) (three specimens). Most larvae were found in the bark of trunks and branches, while pupae and adults were mainly found in the sapwood.
Primeiro registro de Cerambycidae (Coleoptera) em cardeiro (Scleronema micranthum) (Bombacaceae) na Amazônia Central
Keywords: Cerambycidae; Coleoptera; Jamesia; Lamiinae; Malvaceae; Onciderini; Scleronema Micranthum